An Azobenzene-Clamped Bichromophore - Schmickler, Nils; Hofmeister, David A.; Bahr, Joshua; Schedlbauer, Jakob; Jester, Stefan-S.; Lupton, John M.; Höger, Sigurd (Organic Materials, 2022)
An azo-clamped nanoscale bichromophoric cyclophane is synthesized by the intramolecular Pd(II)-catalyzed coupling of the corresponding bisacetylenic precursor. The two azo moieties in the latter can adopt cis and trans configurations. Thin-layer chromatography shows only two spots, and by scanning tunneling microscopy the trans/trans and cis/cis isomers are found. The final cyclophane does not show any switching behavior at all, but dense and wide structures are visualized after adsorption to highly oriented pyrolytic graphite. Photophysical investigations of the cyclophane show that most of the fluorescence is quenched, most likely due to the azo clamp. However, bright molecules show nearly perfect single-photon emission, meaning that efficient energy transfer between the two chromophores takes place within the molecule.
Keywords: cyclophanes; azo-switches; phenylene–ethynylene–butadiynylenes; scanning tunneling microscopy; single-molecule spectroscopy